Segregation, clustering, and suppression of phase separation in amorphous silicon–germanium alloys - Tzoumanekas, Christos; Kelires, Pantelis C. (My University, 2000)
We study the problem of decomposition in amorphous Si-Ge alloys. Our Monte Carlo (MC) simulations show that phase separation is totally suppressed in the amorphous phase. Still, in the short-range structure of the network there is a tendency for clustering of homopolar bonds, as this relieves strain energy. The strain field due to the amorphous/ crystalline interface produces compositional modulations in the alloy.
Keywords: Germanium; Silicon; Alloys